Does the initiation of urate lowering treatment during an acute gout attack prolong the current episode and precipitate recurrent attacks: a systematic literature review - Eminaga, Fatma; Le-Carratt, Jonathan; Jones, Adrian; Abhishek, Abhishek (Springer, 2016)
Objectives: To systematically review the literature on effect of initiating urate lowering treatment (ULT) during an acute attack of gout on duration of index attack and persistence on ULT. Methods: OVID (MEDLINE), EMBASE and AMED were searched to identify randomized controlled trials (RCTs) of ULT initiation during acute gout attack published in English language. Two reviewers appraised the study quality and extracted data independently. Standardised mean difference (SMD) and relative risk (RR) were used to pool continuous and categorical data. Meta-analysis was carried out using STATA v14. Results: 537 studies were selected. 487 titles and abstracts were reviewed after removing duplicates. Three RCTs were identified. There was evidence from two high quality studies that early initiation of allopurinol did not increase pain severity at days 10 to 15 (SMDpooled (95%CI) 0.18(-0.58, 0.93)). Data from three studies suggested that initiation of ULT during an acute attack of gout did not associate with drop-outs (RRpooled (95%CI) 1.16(0.58, 2.31)). Conclusion: There is moderate-quality evidence that the initiation of ULT during an acute attack of gout does not increase pain severity and risk of ULT discontinuation. Larger studies are required to confirm these findings so that patients with acute gout can be initiated on ULT with confidence.